Doubt in the Transaction - Alireza Alipanah; Abbas Majedi (آموزه‌‌های فقه مدني)
“Doubt in the transaction” occurs when the definite conclusion of the two parties of the transaction concern to uncertain parts of two or more than to things. The majority Shiite jurisprudents, as well as some jurists have prohibited the uncertainty in transaction and considered it to be harmful for reasons such as consensus, invoking to some narrations, the impossibility of availability of uncertain thing, ambiguity, risk, non-applicability of such transactions, foolishness of this act, analogous to uncertain compromising, and incorrectness of the concluding of the contract. Iran’s civil law, following the majority, has necessitated “the defined subject” for the correctness of the transaction. By criticizing the reasons of the prohibition of doubting in transaction, and also by referring to reasons such as generalities, invoking to the traditions regarding marriage, uncertain testament and vow, the present article has determined the validity of the transaction that its subject is uncertain and made possible spreading its validity to the assumption that the collection that consists of the things that have different prices. And in the end, it has suggested two solutions of stipulation and drawing lots for determining the subject of the transaction.